ANALISIS IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN BIOLOGI MATERI PERUBAHAN LINGKUNGAN KELAS X DI SMA NEGERI 8 PEKANBARU - Alawiyah Alawiyah; Wan Syafi’i; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to analyze the implementation of the independent curriculum at SMAN 8 Pekanbaru. This research was conducted at SMAN 8 Pekanbaru. When this research starts in April-May 2023. This research is a type of qualitative research. The qualitative research method is a method in which the researcher is the key instrument and examines the condition of natural objects. The average result for teacher planning is 100% in the very good category. The results of the implementation of learning for teachers with a score of 100% are very good categories while for students with a score of 81% the category is very good. The results of the assessment on the teacher got a score of 93% in the very good category while students with a score of 90% were in the very good category. Based on the results of research on the analysis of the implementation of the independent curriculum in learning biology material for class X environmental change at senior high school 8 Pekanbaru, it can be concluded that it is classified as very good.Key Word: Independent Curriculum, Biology Learning, Environmental Influence